Duodenal microbiota dysbiosis in functional dyspepsia and its potential role of the duodenal microbiota in gut–brain axis interaction: a systematic review - Zhang, Xueping; Chen, Lei; Zhang, Tao; Gabo, Ryu; Wang, Qianying; Zhong, Zhuotai; Yao, Mengxi; Wei, Wei; Su, Xiaolan (Frontiers in Microbiology, 2024)
BACKGROUND & AIMS Functional dyspepsia (FD) is a common gastrointestinal disorder associated with brain-gut interaction disturbances. In recent years, accumulating evidence points to the duodenum as a key integrator in dyspepsia symptom generation. Investigations into the pathological changes in the duodenum of FD patients have begun to focus on the role of duodenal microbiota dysbiosis. This review summarizes duodenal microbiota changes in FD patients and explores their relationship with brain-gut interaction dysregulation. METHODS Ten databases including PubMed, MEDLINE, and Cochrane Library were searched up from inception to October 10th, 2023, for clinical interventional and observational studies comparing the duodenal microbiota of FD patients and controls. We extracted and qualitatively summarized the alpha diversity, beta diversity, microbiota composition, and dysbiosis-related factors. RESULTS A total of 9 studies consisting of 391 patients with FD and 132 non-FD controls were included. The findings reveal that the alpha diversity of the duodenal microbiota in FD patients does not exhibit a significant difference when compared to non-FD controls, albeit an upward trend is observed. Furthermore, alterations in the duodenal microbiota of FD patients are associated with the symptom burden, which in turn, impacts their quality of life. In FD patients, a considerable number of duodenal microbiota demonstrate a marked ascending trend in relative abundance, inclusive of taxa such as including phylum Fusobacteria, genera Alloprevotella, Corynebacterium, Peptostreptococcus, Staphylococcus, Clostridium and Streptococcus. A more pronounced declining trend is observed in the populations of genera Actinomyces, Gemella, Haemophilus, Megasphaera, Mogibacterium, Selenomonas within FD patients. A negative correlation in the relative abundance of changes between Streptococcus and Prevotella is identified, which correlates with the severity of symptom burden in FD patients. Moreover, the alterations in specific microbial communities in patients with FD and their potential interactions with the gut-brain axis merit significant attention. CONCLUSION Microbial dysbiosis in FD patients is linked to the onset and exacerbation of symptoms, and is related to the disorder of gut-brain interaction. Larger-scale, higher-quality studies, along with comprehensive meta-omics research, are essential to further elucidate the characteristics of the duodenal microbiota in FD patients and its role in FD pathogenesis. PROSPERO registration number CRD42023470279.